2020
DOI: 10.1016/j.jenvman.2020.110988
|View full text |Cite
|
Sign up to set email alerts
|

Emissions down the drain: Balancing life cycle energy and greenhouse gas savings with resource use for heat recovery from kitchen drains

Abstract: Although the food service sector is a major user of water, the potential for heat recovery from commercial kitchens' drain water remains largely unexplored. For the first time, we compare the life cycle environmental burdens of producing and installing a heat recovery system with the environmental credits arising from energy savings for a restaurant case study, and for the entire UK food service sector. Life Cycle Assessment was applied to determine the impacts of heat recovery systems made from different mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Thermal energy recovery directly from wastewater, applying, for example, heat pumps, is also being considered as an option, and some scholars are focusing their research on that aspect [43][44][45].…”
mentioning
confidence: 99%
“…Thermal energy recovery directly from wastewater, applying, for example, heat pumps, is also being considered as an option, and some scholars are focusing their research on that aspect [43][44][45].…”
mentioning
confidence: 99%
“…Drain water heat recovery therefore offers the opportunity to decarbonise thermal energy consumption in food services. This work is based on previous research from [15,16] on the drain water heat recovery potential and its technical, environmental, and financial aspects in the widely unexplored field of commercial kitchens. A study by [15] found that approximately 1.4 TWh of heat could be recovered every year in the UK food service sector, 90% of which could be achieved in a financially feasible way.…”
Section: Heat Recovery For Ghg Mitigationmentioning
confidence: 99%
“…Ecological construction materials are usually associated with innovation in manufacturing processes having incenting GPP with positive effects on a sustainable environment. GPP facilitates sustainable infrastructure for the agri-food sector (e.g., in rooftop farming) [59][60][61][62][63][64][65][66]…”
Section: Urban Sustainability; Building Design and Constructionmentioning
confidence: 99%
“…The circular economy principles are met in a sustainable city in all of the building's development and utilization stages: (a) construction materials development process (all the actions needed in production from supply to transport and manufacturing), (b) edifice construction stage (the same actions as in stage a), (c) usage stage (renovation, conservation, energy losses, and restoration) and, (d) end-of-life (clearance and recycling). The utilization stage seems to be more expensive, due to the heating and cooling energy requirement [60,61,65]. The operational energy needs may be reduced also by using fossil ammunition or using electricity for lighting, but an important percentage of the energy needs should be reduced by using sustainable building materials.…”
Section: Urban Sustainability In Building Design and Constructionmentioning
confidence: 99%